Systemic sclerosis – prognostic factors, disease activity and severity - Lis-Święty, Anna; Brzezińska-Wcisło, Ligia (Dermatology Review/Przegląd Dermatologiczny, 2010)
Systemic sclerosis is a connective tissue disease characterized by heterogeneous clinical picture, course and prognosis. It is hard to evaluate severity of the disease in individual clinical cases. There are not distinct phases of disease flare and remission. Lesions resulting from the inflammatory process (active disease), and from fibrosis (irreversible damage), can occur. Introduction to clinical practice of new biomarkers could be helpful for determination of indications for intensive immunosuppressive treatment and evaluation of its efficacy.